A imprensa brasileira e a política cardenista (1934-1940) - Martins, Willian Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this study was analysed the speech propagated by the newspapers O Estado de S. Paulo and Correio da Manhã about Cadernism and the government of Lázaro Cárdenas del Río, Mexico's president between 1934 and 1940. Primarily the objective is to understand and evaluate how these organs of Brazilian press conceived and reflected in Cardenist practices and politics, as well as examine how Mexican experiences were related to a series of discussions that permeated Brazilian development in 1930's. Also we intend to compare the speeches provided by both newspapers, finding out how the different trends supported by the writers influenced and guided the productions concerning to Cadernism

Neste trabalho, analisamos o discurso propagado pelos periódicos O Estado de S. Paulo e Correio da Manhã acerca do cardenismo, ou seja, o governo de Lázaro Cárdenas del Río, presidente do México entre os anos de 1934 e 1940. Primordialmente, objetivamos compreender e avaliar como estes órgãos da imprensa brasileira conceberam e repercutiram sobre as práticas políticas cardenistas, bem como examinar em que medida as experiências mexicanas foram relacionadas a uma série de discussões que permeavam o desenvolvimento brasileiro nos anos 1930. Também pretendemos comparar os discursos fornecidos por ambos os jornais, averiguando de que modo as diferentes tendências políticas sustentadas pelos núcleos diretores influenciaram e orientaram as produções concernentes ao cardenismo
Keywords: Vargas, Getulio 1883-1954; Presidentes - Brasil; Imprensa; Mexico - Politica e governo - Séc. XX; Press